Implementing pharmacy-located HPV vaccination: findings from pilot projects in five U.S. states - William A. Calo; Parth D. Shah; Melissa B. Gilkey; Robin C. Vanderpool; Sarah Barden; William R. Doucette; Noel T. Brewer (Taylor & Francis Group, 2019)
Pharmacies are promising alternative settings for human papillomavirus (HPV) vaccination because of their population reach, convenience, and existing infrastructure for vaccine delivery. However, pharmacies in the US are rarely used for adolescent HPV vaccination. We sought to document challenges and opportunities of implementing pharmacy-located HPV vaccination services in five US states by mapping process evaluation results onto key implementation science constructs: service penetration, acceptability, appropriateness, feasibility, fidelity, adoption, and sustainability. Pilot projects were planned in North Carolina (k = 2 pharmacies), Michigan (k = 10), Iowa (k = 2), Kentucky (k = 1), and Oregon (no pharmacy recruited) with varying procedures and recruitment strategies. Sites had open enrollment for a combined 12 months. Despite substantial efforts in these states, only 13 HPV vaccine doses were administered to adolescents and three doses to age-eligible young adults. We identified two major reasons for these underperforming results. First, poor outcomes on service penetration and appropriateness pointed to engagement barriers: low parent demand and engagement among pharmacy staff. Second, poor outcomes on feasibility, adoption, and sustainability appeared to result from administrative hurdles: lacking third party reimbursement (i.e., billing commercial payers, participation in Vaccines for Children program) and limited integration into primary care systems. In summary, pilot projects in five states all struggled to administer HPV vaccines. Opportunities for making pharmacies a successful setting for adolescent HPV vaccination include expanding third party reimbursement to cover all vaccines administered by pharmacists, increasing public awareness of pharmacists' immunization training, and improving care coordination with primary care providers.